Supporting teachers and trainers for successful reforms and quality of VET : Germany - Hensen-Reifgens, Kristina Alice [Verfasser]; Hippach-Schneider, Ute [Verfasser] (My University, 2015)
This article is the fourth one of a set of articles prepared within Cedefop's ReferNet network. It "focuses mainly on teachers and trainers within dual training as well as teachers in full-time vocational schools". Finally, it provides a brief description of staff acting as teachers or trainers in continuing vocational education and training (CVET). (Authors' abstract, BIBB-Doku)
Keywords: P 3.2 Lehrpersonal; Bildungspersonal; Ausbilder; Berufsschullehrer; Weiterbildner; Ausbilderqualifizierung; Professionalität